The Relationship between Perceptions of Online Learning and Self-Regulation of Mathematics Education Students - Hesty Marwani Siregar; Titi Solfitri; Syarifah Nur Siregar (Didaktik Matematika, 2021)
Students' perceptions of learning influence the achievement of learning objectives. With the current online learning, students need to have good self-regulation to obtain excellent learning outcomes. Therefore, this study aims to examine the relationship between perceptions of online learning and the self-regulation of Mathematics Education students during the COVID-19 pandemic. The subject of this research is 121 students in semesters 2, 4, and 6 of the Mathematics Education Program in One University in Indonesia. Students in that semester are students who have experienced both face-to-face lectures and online lectures. To collect data in the study, researchers use questionnaires. This study uses descriptive statistical and quantitative analysis techniques. The results showed that student perception of online learning was correlated to student self-regulation during the COVID-19 pandemic (r=0.545 or moderate correlation). It means when students have a good perception of online learning, their self-regulation tends to be good, vice versa. Thus, one way to improve student self-regulation is by increasing student perceptions of online learning.